2007
DOI: 10.4321/s1886-36552007000200002
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists’ views on involvement in pharmacy practice research: Strategies for facilitating participation

Abstract: *In order for community pharmacy practice to continue to evolve, pharmacy practice research on potential new services is essential. This requires the active participation of community pharmacists. At present the level of involvement of community pharmacists in pharmacy practice research is minimal. Objectives: To ascertain the attitudes of a group of research-experienced community pharmacists towards participating in research; to investigate the barriers and facilitators to participation; to identify potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
117
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(136 citation statements)
references
References 3 publications
18
117
1
Order By: Relevance
“…In a systematic review of 15 studies completed in the UK, Australia, and Canada, the barriers were: lack of time and workload; insufficient or lack of funds; and lack of research knowledge, training, mentorship, and support. [3] Armour et al reported the barriers to research participation were pharmacists' mindsets, communication, infrastructure (time, money, and staff), and skills/knowledge [12]. In Japan, community pharmacists have similar barriers to practice research participation.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of 15 studies completed in the UK, Australia, and Canada, the barriers were: lack of time and workload; insufficient or lack of funds; and lack of research knowledge, training, mentorship, and support. [3] Armour et al reported the barriers to research participation were pharmacists' mindsets, communication, infrastructure (time, money, and staff), and skills/knowledge [12]. In Japan, community pharmacists have similar barriers to practice research participation.…”
Section: Discussionmentioning
confidence: 99%
“…where pharmacists could read about upcoming research projects and sign up to receive e-mails on research topics of interest as one possible way of raising awareness and promoting participation. 14 An Internet-based network for pharmacists interested in research might address some of the barriers preventing pharmacists from becoming involved in research and make them more willing to take part in research projects.…”
Section: Mise En Pratique Des Connaissancesmentioning
confidence: 99%
“…2 This unpreparedness may be due to their mind-set, knowledge and skills, as well as infrastructure requirements. 2 Can some of these barriers be addressed in undergraduate pharmacy programs?…”
Section: Editorialsmentioning
confidence: 99%
“…An estimated 50% of patients with chronic disease do not take their medicines as prescribed. 1,2 Despite an extensive and evolving literature on adherence, and a focus in professional practice, the extent of nonadherence has changed little in four decades. This has significant ramifications for health outcomes and resources.…”
Section: Adherence and Beliefsmentioning
confidence: 99%
See 1 more Smart Citation